Regulating Preimplantation Genetic Diagnosis in the United States - Bayefsky, M. author. aut Link
VIII, 113 p.
Keywords: Reproductive technology allows us to test embryos' genes before deciding whether to transfer them to a woman's uterus. Embryo selection raises many ethical questions but is virtually unregulated in the United States. This comprehensive study considers the ethical, medical, political, and economic aspects of developing appropriate regulation.